A Symphonic Character of the Semiotic Representations - Silveira, Lauro Frederico Barbosa da (2013)
The mediatory function of representation, while representing something to the conduct, supposes the possibility of infinite equally valid theories whose choice of depends of a primary affection between the object, the sign and the conduct. Any object imposes a theory, but appealing to the mind , it gives rise into it the original and poetic production of a representamen. If adequately worked on the development of representation of the object, there will be so many theories on it as the number of original hypotheses. By the other hand, no sign will be coextensively confounded with the object it represents, so that no representamen can be intended to be the unique and exclusive one of the object it represents. Choosing a theory depends not only of the concrete context that gives place to it, but also of the originality with which il lume naturale express itself in each mental synthesis. It also depends of the destiny potentially present in the representation, and that is searched as an ideal, becoming effective in the vicissitude of concretely acting. The plurality of theories, settled as a great symphony, is under several aspects the very expression of a free and originally poetic reason, whose nature is irreducibly cosmic and social.